Spontaneous rupture of hepatic metastasis as the initial presentation of gastric hepatoid adenocarcinoma: a rare case report and literature review - Zhou, Bin; Lu, Yingchao; Zhang, Juan; Yang, Guobiao; Xu, Hongxing; Shen, Danfeng (Frontiers in Oncology, 2026)
Hepatoid adenocarcinoma (HAC) is an extremely rare and highly malignant tumor with histological features resembling hepatocellular carcinoma but originating from extrahepatic organs, most commonly in the stomach, known as gastric hepatoid adenocarcinoma (GHA). Spontaneous rupture of hepatic metastasis as the initial presentation of GHA is even rarer, posing significant challenges for clinical diagnosis and management. We present a case of a 74-year-old male admitted to the hospital for right upper abdomen pain. Through a combination of imaging, laboratory tests, interventional therapy, and pathological biopsy, the ultimate diagnosis was confirmed as GHA with spontaneous rupture of hepatic metastasis. The patient was transferred for chemotherapy and immunotherapy following transcatheter arterial embolization (TAE). We systematically reviewed relevant literature and summarized the clinical characteristics, diagnostic methods, treatment strategies, and prognosis of GHA with ruptured hepatic metastases. For patients with ruptured liver tumors, a comprehensive assessment of the potential primary site is essential to avoid misdiagnosis. TAE may create opportunities for subsequent curative surgery, chemotherapy, immunotherapy, and targeted therapy, potentially leading to an overall survival benefit. This case report aims to help clinicians gain a deeper understanding of this rare disease, thereby enabling early diagnosis and optimizing treatment strategies.